(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research draws its importance from identifying the methods of profit management in misleading the financial statements, which in turn is reflected in the decisions of the authorities that relied on these reports, and then the models that help in detecting those methods used by the auditors. Risks. The index (margin of excess cash) was used to detect profit management practices on a group of banks listed in the Iraqi market for securities and the number of (23) banks, including (12) commercial bank and (11) Islamic bank and the results were compared to commercial banks with Islamic banks.((The research started from the hypothesis that the use of the (excess cash margin) model in the banking sector reveals the management of profits in the financial statements and helps the regulators to reduce these practices and develop appropriate corrective measures and achieve the objectives of the users of the financial statements)). Analytical. The research has reached a set of conclusions, the most important of which is that all the research sample banks listed in the Iraq Stock Exchange have exercised the management of profits at different rates during the research period. Moreover, Islamic banks were higher than commercial banks in profit management, and the research recommended the need to rely on this model to minimize the impact of profit management practices.